Recurrent fifth metatarsal stress fractures in a professional soccer player with hypoparathyroidism: a case report - Itaru Kawashima; Atsushi Yamaga; Ryosuke Kawai; Yushi Hoshino; Shinya Ishizuka (BMC Musculoskeletal Disorders, 2020)
Abstract Background Hypoparathyroidism is characterized by low or inappropriately normal levels of parathyroid hormone leading to hypocalcemia. In this report, a case of recurrent fifth metatarsal stress fractures in a professional soccer player with hypoparathyroidism is presented. Case presentation A 23-year-old male professional soccer player developed left foot pain. He had no specific medical or family history. He was diagnosed with a fifth metatarsal stress fracture and underwent osteosynthesis with a cannulated cancellous screw 3 days after the injury. After three and a half months, the X-ray showed bone union, and he returned to full sports activity. However, he felt pain in his left foot again, and a re-fracture was found on X-ray a week later. Osteosynthesis was performed again. Two months after re-operation, the cause of re-fracture was investigated. Laboratory results showed abnormally low levels of serum calcium (8.4 mg/dL) and intact parathyroid hormone (i-PTH: 19.0 pg/mL). However, other laboratory examinations were normal. Therefore, he was diagnosed with primary hypoparathyroidism according to the diagnostic criteria. Medical treatment was started with alfacalcidol 1.0 μg/day. One month after starting medication, the serum calcium improved to 9.4 mg/dL. Four months after the re-operation, the X-ray showed bone union, and he was therefore allowed to play soccer. While he played professional soccer, there were no new subjective complaints. Conclusions Hypoparathyroidism may be one of the risk factors for stress fractures. We believe that serum calcium levels should be checked in patients with stress fractures, and if the serum calcium is low, hypoparathyroidism should be considered.